2000
DOI: 10.1002/(sici)1096-8628(20000207)96:1<102::aid-ajmg20>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

COMT andDRD3 polymorphisms, environmental exposures, and personality traits related to common mental disorders

Abstract: In a community sample of 2,327 Caucasians, we tested the hypotheses that polymorphisms in the COMT and DRD3 genes are associated with personality traits conferring vulnerability to anxiety, depression, or alcohol misuse, or with current symptoms of these; and that the association is stronger in persons who also have been exposed to stressor experiences. To conserve resources and to allow replication, the genetic analysis was undertaken in two stages. For the COMT polymorphism, no statistically significant asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 50 publications
5
42
0
1
Order By: Relevance
“…et al, 2003), neuroticism (Eley et al, 2003) (but not in all studies; Henderson et al, 2000), and aggression (Rujescu et al, 2003). It has also been strongly associated with one anxiety disorder in particularFpanic disorder ( (Ohara et al, 1998;Samochowiec et al, 2004) and, according to a recent meta-analysis, not with obsessive-compulsive disorder (Azzam and Mathews, 2003).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…et al, 2003), neuroticism (Eley et al, 2003) (but not in all studies; Henderson et al, 2000), and aggression (Rujescu et al, 2003). It has also been strongly associated with one anxiety disorder in particularFpanic disorder ( (Ohara et al, 1998;Samochowiec et al, 2004) and, according to a recent meta-analysis, not with obsessive-compulsive disorder (Azzam and Mathews, 2003).…”
Section: Discussionmentioning
confidence: 96%
“…Two recent meta-analyses (that included a substantially overlapping set of studies) found evidence of an association between 5-HTTLPR and neuroticism, although less so with other anxiety-related constructs (eg harm avoidance) (Schinka et al, 2004;Sen et al, 2004a). Other genes tested for an association with anxiety-related traits have included monoamine oxidase type A (Eley et al, 2003;Jorm et al, 2000), cytochrome P450 2D6 isoenzyme (Roberts et al, 2004), GABA-A receptor alpha-6 subunit (Sen et al, 2004b) and, in a number of studies, catechol-O-methyltransferase (COMT) (Eley et al, 2003;Enoch et al, 2003;Henderson et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, this appears to be somewhat at odds with a number of prior studies of neuroticism and other anxiety-related traits and symptoms (see Table 1). While several of the smaller studies reported marginally significant associations with the met allele or met-met genotype, the two largest studies either found no association with this locus (62) or association with the opposite (val) allele (4). Among those studies, only Stein and colleagues examined the effects of markers other than rs4680 (7).…”
Section: Discussionmentioning
confidence: 99%
“…No evidence of association with alcoholism was found in a case-control study from Japan 10 and no association with personality traits conferring vulnerability to alcoholism was found in a community sample from Australia. 11 To further investigate the role of the COMT lowactivity allele in alcoholism and extend the analysis to alcoholism with early onset, we tested the transmission of low-vs high-activity alleles from parents to alcoholic offspring. The use of a family-based association approach avoids the problem of case-control association studies in which false positive results can be produced as a result of hidden population stratifications.…”
Section: Catechol-o-methyltransferasementioning
confidence: 96%